2019
DOI: 10.1007/s13592-019-00658-z
|View full text |Cite
|
Sign up to set email alerts
|

Different activation of immune-related genes in honey bee nurses and foragers (Apis mellifera)

Abstract: Honey bee workers show very flexible aging patterns. Their typical behavioral progression, from nurse bees to forager bees, is associated with an onset of aging symptoms. Here, we studied how immune-activation can affect nurse and forager bees differently. Nurse and forager bees of identical chronological age were injected with vehicle control or the bacterial cell wall components lipopolysaccharide (LPS) or peptidoglycan (PGN). Next, we monitored survival and tested the expression of three immune-related gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Hence, both in terms of haemocyte number and their immunocompetence, Imidacloprid exposure had a significant negative impact, but was corrected by 670nm exposure ( Fig 2 ). Additionally, challenging the immune system of the bee leads to attrition within the 24 h immune response period [ 55 ]. In the control group, 35% of the original cohort died, 50% in the Imidacloprid group died, whilst there was no deaths post immune challenge within 24h, in the two groups exposed to 670nm light.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, both in terms of haemocyte number and their immunocompetence, Imidacloprid exposure had a significant negative impact, but was corrected by 670nm exposure ( Fig 2 ). Additionally, challenging the immune system of the bee leads to attrition within the 24 h immune response period [ 55 ]. In the control group, 35% of the original cohort died, 50% in the Imidacloprid group died, whilst there was no deaths post immune challenge within 24h, in the two groups exposed to 670nm light.…”
Section: Resultsmentioning
confidence: 99%
“…Preserved haemocyte numbers account for the larger inhibition zones, as more anti-microbial peptides could be secreted into the haemolymph in response to immune challenge [ 64 ]. The immune challenge model employed triggers an immune response from both exposure to bacterial antigens, and wounding resulting from the injection [ 55 ]. In this instance we do not know which is predominating, however we have shown that Imidacloprid decreases the antimicrobial activity of the haemolymph, and that 670 nm light can restore immunocompetency.…”
Section: Discussionmentioning
confidence: 99%
“…The versatile activities of workers expose them to pathogens with significant effects such as paralysis, respiratory failure, and mortality of target (workers) and non-target (e.g., drones and queens) individuals. The A. mellifera workers need a highly adapted system as the tasks they perform during their lifespan expose them to distinct pressures from pathogenic exposure [46] . In general, the first line of defense against most pathogens is the cuticle, a preventive barrier designed to prevent or retard the entry of pathogens into the haemoceol [47] , [48] .…”
Section: Discussionmentioning
confidence: 99%
“…The qPCR was performed using a CFX connect RT-PCR detection system (Bio-Rad Laboratories), and each reaction contained 0.5 µL of 10 µM of each primer, 12.5 µL of SYBR Green (170-8882; Bio-Rad Laboratories), 1 µL of diluted cDNA, and 10.5 µL of ddH 2 O in a final volume of 25 µL. The β-actin gene was used as a reference gene when measuring gene expression in honey bees [16,25,[28][29][30]. The primers were designed according to GenBank's nucleotide sequences, and primer sequences are shown in Table 1.…”
Section: Rna Isolation and Quantitative Real-time Polymerase Chain Re...mentioning
confidence: 99%
“…Defensin-1 is synthesized in salivary glands, and defensin-2 is synthesized in the fat body and lymph [11]. Defensins were used to assess the impact of Metarhizium anisopliae infection, lipopolysaccharide, and peptidoglycan on the immunity of honey bees [15,16]. The genes and proteins of abaecin, defensin-2, and hymenoptaecin are used to evaluate the humoral immunity of honey bees [3][4][5].…”
Section: Introductionmentioning
confidence: 99%